PHILOSOPHICAL SCIENCE FRAMEWORK SUPPORTING STRATEGIC INNOVATION TO IMPROVE PRIVATE UNIVERSITY MANAGEMENT - Endang Tri Pujiastuti (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
This study explores how the philosophy of science can serve as a rational foundation for strategic innovation in managing private universities in Indonesia. The research is driven by the observation that many innovation management policies in private universities remain largely technical and lack a reflective, philosophical basis. Using a systematic review of SINTA-indexed and international journal articles published between 2021 and 2025, this study examines how the ontological, epistemological, and axiological dimensions of the philosophy of science relate to institutional innovation indicators such as intellectual property management, industry collaboration, and university governance. The findings show that the ontological dimension helps universities define research directions and institutional goals that align with academic realities. The epistemological dimension strengthens approaches to validating knowledge and advancing research outcomes, while the axiological dimension underlines the importance of accountability, collaboration, and ethical values in university management. Overall, this study highlights that incorporating philosophical perspectives into strategic innovation provides a rational and sustainable framework for improving the quality and competitiveness of private universities in Indonesia the findings indicate that the integration of the three dimensions of the philosophy of science provides both a rational and normative foundation for strategic innovation in private universities. The philosophy of science functions not only as a reflective theory but also as a conceptual framework that strengthens policy effectiveness, social legitimacy, and the sustainability of institutional innovation. Theoretically, this study contributes by proposing an integrative model that links the philosophical foundations of science with innovation performance indicators. Practically, it offers an evaluative instrument for university leaders to assess the alignment between institutional values and the strategic direction of innovation. Therefore, the philosophical approach to science serves as a rational foundation that ensures higher education innovation is systematic, sustainable, and oriented toward values.